Polydopamine Nanomaterials: Recent Advances in Synthesis Methods and Applications - Ball, Vincent (Frontiers in Bioengineering and Biotechnology, 2018)
Polydopamine (PDA), the final oxidation product of dopamine or other catecholamines, attracted much attention as versatile coatings that can be used to cover the surface of almost all materials with a conformal layer of adjustable thickness ranging from a few to about 100 nm. These PDA layers can be subsequently modified with molecules carrying nucleophilic groups or with metallic nanoparticles from solutions containing metallic cations. However, during the deposition of PDA film on the surfaces, the reaction products that are simultaneously obtained from the oxidation of catecholamines in solution precipitate. Hence, some recent effort has been devoted to produce PDA in the form of nanoparticles. The aim of this short review is to give a comprehensive description of the synthesis methods yielding of PDA nanoparticles in the absence or in the presence of templating agents (polymers, polyelectrolytes, surfactants, proteins, and even some small organic molecules). We will also describe the use of thin PDA layers to coat already synthesized nanoparticles or nanotubes. Finally, several first applications of the obtained PDA nanoparticles will be described.